The Role of Yasawiyya in Kyrgyz’s Acceptance of Islam and its Place in Kyrgyz Culture - KADYROV, Mederbek (Scientific Journal of Faculty of Theology, 2018)
Yasawiyya, combining the steppe culture with the Islamic culture, played an important role in Kyrgyz’s acceptance of Islam. Ahmet Yasawi’s Hikmat and his student Süleyman Bakırgani's work Ahir Zaman were widely read among the Kyrgyz. With these characteristics, Yasawiyya has deeply influenced Kyrgyz culture along with Kyrgyz's understanding of Islam. It is possible to see clearly the effects of Yasawiyya on the works of the Kyrgyz poets.